1990
DOI: 10.1002/jmor.1052040204
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the kidney in the crab‐eating frog, Rana cancrivora

Abstract: The structure of the nephron in the ranid frog, Rana cancrivora, was studied by light and electron microscopy. This frog is the only amphibian species to live in mangrove swamps of very high salinity. The nephron consists of the following parts: renal corpuscle, ciliated neck segment, proximal tubule, ciliated intermediate segment, distal tubule, connecting tubule, and collecting duct. The distal tubule is located in the ventromedial region of the kidney, and the other tubules are situated in the dorsolateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…The structural features of amphibian mesonephric tubules described in classical papers (Policard 1910;Stewart 1927;Gerard and Cordier 1932) have been confirmed in some ultrastructural studies (Linss and Geyer 1964a, b;Wake 1970;Meseguer et al 1978a, b;Taugner et al 1982;Sakai et al 1986;Uchiyama et al 1990). However, there is no information on the ontogenesis of this mesonephric tubule in the tadpole kidney during larval and metamorphosis stages.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The structural features of amphibian mesonephric tubules described in classical papers (Policard 1910;Stewart 1927;Gerard and Cordier 1932) have been confirmed in some ultrastructural studies (Linss and Geyer 1964a, b;Wake 1970;Meseguer et al 1978a, b;Taugner et al 1982;Sakai et al 1986;Uchiyama et al 1990). However, there is no information on the ontogenesis of this mesonephric tubule in the tadpole kidney during larval and metamorphosis stages.…”
Section: Discussionmentioning
confidence: 49%
“…1978a,b;Taugner etal. 1982;Sakai and Kawahara 1983;Stanton et al 1984;Sakai et al 1986;Uchiyama et al 1990). However, in spite of the significant morphofunctional changes determined by the freshwater environment and undergone by the kidney during ontogenesis, there are no data on the amphibian mesonephric duct during this period.…”
Section: Introductionmentioning
confidence: 99%
“…The development, morphology and ultrastructure of the amphibian pronephros and mesonephros have been extensively studied [3][4][5][6][7][8][9][10][11][12][13][14][15]. Previous studies [1,[16][17][18][19] on larval and adult amphibians show that the organs involved in the osmoregolatory functions are targets of atrial natriuretic peptide (ANP).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most crucial chemical factors for their successful breeding and development is salinity, because in many amphibian species including those that have a high salinity tolerance in adults (e. g., Rana cancrivora: Gordon et al, 1961), the rate of egg survival or of metamorphosis falls remarkably even with a slight increase in salinity (cordon and Tucker, 1965;Beebee, 1985;Uchiyama et al, 1990;Voigt, 1991). Nonetheless, some amphibians occur in potentially highly saline habitats, such as ponds and streams located within the reach of saltwater spray and tidal movements, and desert ponds where the salinity often remarkably increases with evaporation.…”
mentioning
confidence: 99%
“…For such frogs, it is essential to acquire high salinity tolerance during the embryonic and larval period, or otherwise, the particular ability to avoid breeding at highly saline sites. Indeed, Uchiyama et al (1990) reported that in R. cancrivora living in a coastal marsh, spawning occurs only after heavy rainfall so as to allow eggs an early embryonic development under low salinity condition. For other frogs inhabiting potentially saline habitats, however, no studies have been made regarding their adaptation for successful reproduction.…”
mentioning
confidence: 99%